2005
DOI: 10.1590/s0103-97332005000300017
|View full text |Cite
|
Sign up to set email alerts
|

Generalized uncertainty principle, extra-dimensions and holography

Abstract: We consider Uncertainty Principles which take into account the role of gravity and the possible existence of extra spatial dimensions. Explicit expressions for such Generalized Uncertainty Principles in 4 + n dimensions are given and their holographic properties investigated. In particular, we show that the predicted number of degrees of freedom enclosed in a given spatial volume matches the holographic counting only for one of the available generalizations and without extra dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…This latter implies a minimal position uncertainty ∆x min [4,5,6,7,8]. Moreover, the emergence of this minimal length in non-relativistics quantum mechanics introduces many consequences such as the deformation of the Heisenberg algebra, the loss of the localization of particles in the position representation, the deformation of the structures of the Hilbert space, the noncommutation in position space [4] etc.…”
Section: Introductionmentioning
confidence: 99%
“…This latter implies a minimal position uncertainty ∆x min [4,5,6,7,8]. Moreover, the emergence of this minimal length in non-relativistics quantum mechanics introduces many consequences such as the deformation of the Heisenberg algebra, the loss of the localization of particles in the position representation, the deformation of the structures of the Hilbert space, the noncommutation in position space [4] etc.…”
Section: Introductionmentioning
confidence: 99%
“…According to this, the development of mathematical manipulation to handle the minimal length became a central issue in modern quantum gravity. The several research fields in which the concept of an observable minimal length plays an important role in their complete description are string theory [1][2][3][4][5], loop quantum gravity [6], noncommutative geometry [7], noncommutative field theories [8][9][10], and black-hole physics [11,12]. Standard formulation of quantum mechanics with minimal length for these systems has been carried out starting from the modified Heisenberg algebra with a deformed commutation relation between position and momentum operators, which arises from intrinsic noncommutativity in geometries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, various researches regarding the quantum gravity [3,68] and cosmology [10], string theory [64,65], noncommutative geometry [54], black hole physics [70] and thermodynamics [63] show that a minimal observable length should exist.This minimal length (ML) may be introduced as an additional uncertainty in position measurements ∆x min , which leads to a generalization of Heisenberg's uncertainty principle. Kempf with his collaborators [41,[47][48][49], showed that a ML can be obtained out of the generalized Heisenberg algebra with the form…”
Section: Introductionmentioning
confidence: 99%